2018
DOI: 10.1212/wnl.0000000000004888
|View full text |Cite
|
Sign up to set email alerts
|

Serum caffeine and metabolites are reliable biomarkers of early Parkinson disease

Abstract: ObjectiveTo investigate the kinetics and metabolism of caffeine in serum from patients with Parkinson disease (PD) and controls using liquid chromatography–mass spectrometry.MethodsLevels of caffeine and its 11 metabolites in serum from 108 patients with PD and 31 age-matched healthy controls were examined by liquid chromatography–mass spectrometry. Mutations in caffeine-associated genes were screened by direct sequencing.ResultsSerum levels of caffeine and 9 of its downstream metabolites were significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
62
2
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 38 publications
13
62
2
2
Order By: Relevance
“…16,[36][37][38] DiAcSpd levels clearly correlated with both H&Y and UPDRS-III under age-or medication-normalized conditions, and significantly correlated with FA (an index of white matter integrity alterations), in diffuse white matter, similar to our previous report. Notably, even using a multivariate model, DiAcSpd remained significantly correlated with disease severity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…16,[36][37][38] DiAcSpd levels clearly correlated with both H&Y and UPDRS-III under age-or medication-normalized conditions, and significantly correlated with FA (an index of white matter integrity alterations), in diffuse white matter, similar to our previous report. Notably, even using a multivariate model, DiAcSpd remained significantly correlated with disease severity.…”
Section: Discussionsupporting
confidence: 90%
“…However, surrogate biomarkers reflecting age-related pathogeneses have not been established. 16,[36][37][38] DiAcSpd levels clearly correlated with both H&Y and UPDRS-III under age-or medication-normalized conditions, and significantly correlated with FA (an index of white matter integrity alterations), in diffuse white matter, similar to our previous report. 34,39 Likewise, higher diagnostic power of DiAcSpd levels was confirmed.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, Berg et al., suggested that decreasing caffeine consumption was one of the risks of prodromal iPD . Furthermore, we revealed that serum levels of caffeine and its metabolites are significantly decreased in iPD, despite no difference in caffeine consumption between patients and controls . Interestingly, similar to iPD, our results here also indicate decreased serum levels of caffeine and its metabolites in PARK2.…”
Section: Discussionsupporting
confidence: 76%
“…Screening was also performed for polymorphisms of cytochrome P450 family 1, subfamily A (CYP1A) and cytochrome P450 famil y 2, s ubfamily E member 1 (CYP2E1) , which are involved in metabolism of xenobiotics including caffeine and its metabolites. The genetic analysis methods have been previously described . Data were collected between March 2014 and April 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Although patients with atypical parkinsonism were also taking antiparkinsonian drugs, including levodopa, dopamine agonists, and MAOB inhibitors, the %HNA of these patients was similar to healthy subjects. Additionally, in recent reports, a metabolomics analysis in iPD revealed that antiparkinsonian drugs are less effective on their metabolites; therefore, we consider that antiparkinsonian drugs had little influence on the results. Fourth, a longitudinal study should be conducted to establish a direct association between hyperoxidative albuminemia and disease progression.…”
Section: Discussionmentioning
confidence: 99%